1958
DOI: 10.1002/aja.1001020207
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopy of rat cranial meninges

Abstract: It is a tribute to the monumental character of the work published by Key and Retxius in 1876 that there has been little need to present further anatomical reports concerned with the gross and microscopic morphology of the meninges. Subsequent workers have dealt either with broader problems such as the circulation of the cerebrospinal fluid, or with particular aspects of meningeal anatomy such as the perivascular relations. The present authors have considered the latter problem in another communication (Maynard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

1962
1962
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(48 citation statements)
references
References 11 publications
2
45
0
1
Order By: Relevance
“…The detection oftranscriptional activity ofthe rIGF-II gene in both the arachnoid and pial cells, which cannot be discriminated morphologically (22)(23)(24)(25), suggests that they share at least some common function. However, our data cannot demonstrate whether the IGF-II gene is active in all of the leptomeningeal cells, or in a specific subset [at least two, and possibly more, cellular types constitute the cell population of the leptomeninges (23,24,42)].…”
Section: Resultsmentioning
confidence: 99%
“…The detection oftranscriptional activity ofthe rIGF-II gene in both the arachnoid and pial cells, which cannot be discriminated morphologically (22)(23)(24)(25), suggests that they share at least some common function. However, our data cannot demonstrate whether the IGF-II gene is active in all of the leptomeningeal cells, or in a specific subset [at least two, and possibly more, cellular types constitute the cell population of the leptomeninges (23,24,42)].…”
Section: Resultsmentioning
confidence: 99%
“…The structure of the meninges has been described in numerous studies of animals (Pease and Schultz, 1958;Andres, 1967;Waggener and Beggs, 1967;Klika, 1967;McCabe and Low, 1969;Himango and Low;1971;Akashi, 1972;Allen and Low, 1975;Fiedler and Drommer, 1976;Allen and DiDio, 1977;Nabeshima et al, 1975;Oda and Nakanishi, 1984) and humans (Key and Retzius, 1876;Anderson, 1969;Lopes and Mair, 1974;Rascol and Izard, 1976;Schachenmayr and Friede, 1978;Alcolado et al, 1988). There is no general agreement, however, regarding definition, ultrastructure, and function of the dura-arachnoid junction, i.e., the meningeal layer referred to by Nabeshima et al (1975) as the "dural border layer," but tentatively identified here as the "subdural compartment" (SDC).…”
mentioning
confidence: 94%
“…To distinguish between meningeal cells and the closely apposed fibroblasts, we wanted to identify a specific marker for meningeal cells. Unlike that of the fibroblasts (16,32), the embryonic origin of the meninges can be partly traced back to neural ectoderm-derived cells (17,20,29,38), which are known to express cytokeratins (15); this was the rationale for using an antibody against these markers to exclusively immunostain ONP meningeal cells. Immunofluorescence for PrP Sc and cytokeratins on serial tissue sections demonstrated that cytokeratins and PrP Sc colocalized inside the meningeal layer of the ONP (Fig.…”
Section: Using Immunofluorescence For Prpmentioning
confidence: 99%